2017
DOI: 10.1111/risa.12950
|View full text |Cite
|
Sign up to set email alerts
|

Using the CAUSE Model to Understand Public Communication about Water Risks: Perspectives from Texas Groundwater District Officials on Drought and Availability

Abstract: Public communication about drought and water availability risks poses challenges to a potentially disinterested public. Water management professionals, though, have a responsibility to work with the public to engage in communication about water and environmental risks. Because limited research in water management examines organizational communication practices and perceptions, insights into research and practice can be gained through investigation of current applications of these risk communication efforts. Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Less is known about how institutional communication structures and processes might facilitate or hinder interdisciplinary research. Some research indicates that while decentralized communication structures might empower employees to participate in and feel responsibility for an organization's communication efforts, the communication function may become deprioritized out of necessity if decentralization is not accompanied by centralized support, expertise, resources, or accountability (VanDyke and King, 2018). Recent studies have begun examining science communication at the institutional level in universities.…”
Section: Interdisciplinary Researchmentioning
confidence: 99%
“…Less is known about how institutional communication structures and processes might facilitate or hinder interdisciplinary research. Some research indicates that while decentralized communication structures might empower employees to participate in and feel responsibility for an organization's communication efforts, the communication function may become deprioritized out of necessity if decentralization is not accompanied by centralized support, expertise, resources, or accountability (VanDyke and King, 2018). Recent studies have begun examining science communication at the institutional level in universities.…”
Section: Interdisciplinary Researchmentioning
confidence: 99%
“…in-house; consultant; training) should inform how risk communication structures fit in corporate governance and how risk communication is practiced to ensure it is prioritized, practiced with accountability, and able to be evaluated and adjusted in the event objectives are not met. This is particularly important to consider as some research suggests that decentralization of the risk communication function may not be the ideal practice in all situations (VanDyke and King, 2018; Zuidema and de Roo, 2015).…”
Section: Rethinking Communication Decentralizationmentioning
confidence: 99%
“…personnel and/or policies) in organizations because practical limitations often dictate the nature and frequency of an organization’s risk communication planning and programming. For example, VanDyke and King (2018) found that among Texas water district officials working in smaller offices (in some cases offices employed only one person), risk communication programming was decentralized by necessity (rather than a lack of desire) and was often not prioritized due to competing obligations. That is, the risk communication function was often decentralized, informal, and ad hoc, which may have hindered robust risk communication planning and risk manifestation mitigation.…”
Section: Rethinking Communication Decentralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these steps, thus form the acronym. The model has been applied in emergency management context 35 ; physician‐patient communication 36 ; a drug manufacturer's medication recall, 37 and water risk context 38 . We, however, employ the model in a health worker context, by assessing the impact of its goals on the nurses.…”
Section: Introductionmentioning
confidence: 99%